Relationship between parental attachment and adolescent positive well-being with gender as moderating factor - Rajendran, Kogilavani; Juhari, Rumaya (The Writer's Publications, 2018)
The positive development view emphasizes the possibility of adolescents developing positive traits based on their strengths, positive qualities, and supportive environments. Therefore identifying protective factors that could influence the positive well-being of adolescents is important. This study examines the relationship between parental attachment with positive adolescent well-being and the role of gender as a moderator for links between parental attachments with positive adolescent well-being. A total of 400 7th Grade students from government schools in the Federal Territory of Kuala Lumpur and state of Selangor were involved in this study. Adolescent positive well-being and parental attachment were measured using the Positive Youth Development Scale (Geldhof, et al., 2013) and Inventory of Peer and Parent Attachment (Armsden & Greenberg, 1987). The results show that both maternal and paternal attachments are predictors of adolescent positive well-being. The study also found that gender moderated the relationship between paternal attachment and adolescent positive well-being. This study provides information on factors that can help the positive development of adolescents. Identifying these factors will provide insight on events or experiences that will increase the occurrence of positive outcomes and reduce the likelihood of negative outcomes.